Prevention of depression through nutritional strategies in high-risk persons: rationale and design of the MooDFOOD prevention trial - Roca, Miquel (BMC Psychiatry, 2016)
BACKGROUND: Obesity and depression are two prevalent conditions that are costly to individuals and society. The bidirectional association of obesity with depression, in which unhealthy dietary patterns may play an important role, has been well established. Few experimental studies have been conducted to investigate whether supplementing specific nutrients or improving diet and food-related behaviors can prevent depression in overweight persons. METHOD/DESIGN: The MooDFOOD prevention trial examines the feasibility and effectiveness of two different nutritional strategies [multi-nutrient supplementation and food-related behavioral change therapy (FBC)] to prevent depression in individuals who are overweight and have elevated depressive symptoms but who are not currently or in the last 6 months meeting criteria for an episode of major depressive disorder (MDD). The randomized controlled prevention trial has a two-by-two factorial design: participants are randomized to daily multi-nutrient supplement (omega-3 fatty acids, calcium, selenium, B-11 vitamin and D-3 vitamin) versus placebo, and/or FBC therapy sessions versus usual care. Interventions last 12 months. In total 1000 participants aged 18–75 years with body mass index between 25–40 kg/m(2) and with a Patient Health Questionnaire-9 score ≥ 5 will be recruited at four study sites in four European countries. Baseline and follow-up assessments take place at 0, 3, 6, and 12 months. Primary endpoint is the onset of an episode of MDD, assessed according to DSM-IV based criteria using the MINI 5.0 interview. Depressive symptoms, anxiety, food and eating behavior, physical activity and health related quality of life are secondary outcomes. During the intervention, compliance, adverse events and potentially mediating variables are carefully monitored. DISCUSSION: The trial aims to provide a better understanding of the causal role of specific nutrients, overall diet, and food-related behavior change with respect to the incidence of MDD episodes. This knowledge will be used to develop and disseminate innovative evidence-based, feasible, and effective nutritional public health strategies for the prevention of clinical depression. TRIAL REGISTRATION: ClinicalTrials.gov. Number of identification: NCT02529423. August 2015. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12888-016-0900-z) contains supplementary material, which is available to authorized users.